Urbane Illusioni. Riflessioni sul Centro Storico di Napoli - Berritto, Antonella; Gargiulo, Giuseppe; Marotta, Ilaria (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2020)
Urban illusions. Thoughts about Naples’ Old Town The studies carried out in the last decades on the ways people gather together and are attracted by central areas of a city show a change in the idea of a city in itself. Social relationships and creativity become new ways to give a different morphology to the city. Urban regeneration - oriented towards cultural production and consumption - economic development and the revival of prestige through tourism are strategies to plan culturally and economically oriented cities. The issue is that contemporary cities, while enhancing urban diversity, promote «an urban illusion to sell» (Sosa, 2011) and a commercialization of public space, compromising the «common urban dimension» (Harvey, 2013). Social zoning, illusory inclusiveness and fragmented territorial identity are the first results emerging from a research made in Naples. The aim of this work is to think about the transformation of economic urban morphology within one famous square of old town Naples, Piazza Bellini. Starting from the role of social links which place high value in the production, appropriation and perpetual destruction of the urban common.